Progress on the national echinococcosis control programme in China: analysis of humans and dogs population intervention during 2004-2014 - Qing Yu; Ning Xiao; Shuai Han; Tian Tian; Xiao-Nong Zhou (BMC, 2020)
Abstract Background A national control program for echinococcosis has been in effect since 2005 in China. This program has applied a comprehensive strategy, and good control results have been achieved. Human echinococcosis prevalence rate decrease from 1.08% in 2004 to 0.24% in 2012. The objective of this study is focusing on assessment of the programme with two indices, including patient treatment and registered dogs deworming, in endemic areas of echincoccosis control over the period of 10 years (2004-2014) in China. Methods We established the database including demography at county and township levels with coverage for ten provinces and autonomous regions of China in this study. We using methods of epidemiological descriptive, instead the expectation-maximization for missing value filling for grouping available patients into those subjected to surgery and those receiving drug treatment after population screening and the dogs population after registered by deworming. We performed Microsoft Excel software and SPSS software on the results as percentages with the corresponding 95% confidence intervals (95% CIs). We also statistically analyzed the economics data on patient treatment and dogs deworming after the corresponding discount with annual bank interest rates (USD 1 = CNY 6.5, bank discount average changes of 2.3-3.3%). Results During 2004-2014, the grant total average rate of surgical patient (after surgical operation) treatment had increased with 32.4% and with 81.3% for medical treatment with albendazole. Meanwhile, it increased by 58.6% for the deworming of registered dog since 2007. The accumulated costs amounted to USD 27.03 million after discount for patients and registered dog treatment, which is 1/4 of the total accumulated financial inputs (USD 110.67 million from the Chinese Government). Since the implementation of the national program, it has increased 57 times with respect to the annual financial inputs (costs) and 368 times with respect to all accumulated financial inputs (costs). Conclusions This study showed that in endemic areas, patient diagnosis and management, dog management and treatment over this period helped reduce the parasite load to control the disease. More attention should be paid to controlling wild canines during the ongoing program period and sustainable follow-up evaluations are crucial for success and continued implementation of the national program.